Motivation in second language learning: Technology inside and outside classroom - Asiah, Kassim; Ahmad Nasaruddin, Sulaiman (2010)
In this technological age, language learning moves to a point where interactivity is not just between teacher and students in the same room, but with computers and other users outside the four walls of the classroom. In many ways, these digital learning tools help engage learners and encourage awareness of language skills. Aspects of the overall learning process that is worth looked into are the motivation and autonomy of learners in learning second language. A study was carried out to identify features that can enhance ESL learners' independence and motivation using digital materials by adapting Gardner's Attitude/Motivation Test Battery (AMTB). Findings of the study assert that interactivity features are essential in enhancing motivation on one hand, while teacher's facilitation is integral in learning, even with the use of digital tools in activities and tasks. Based on the elements identified in the study, some suggestions are provided with the hope that these findings can be made use of by educators and material developers to better engage students as well increase awareness of the language learnt.